Capacity and Service Innovation In Implementation Government Of Village In Serang District Indonesia - Sukendar, Sukendar; Hasanah, Budi (Indonesian Journal of Social Science Research, 2020)
This article discusses the capacity and innovation of Village Government population services in several villages in Serang District, Indonesia. The research approach used qualitative descriptive with interview data collection techniques, observation and documentation with the informant determination technique through purposive sampling. The results of the research findings indicate that capacity and service innovation are the most energetic parts of the implementation of village governance. In this case, it is important to encourage the performance of village government, especially in increasing the capacity and governance of public service innovation in several villages in Serang District.